Numerical Study of Savonius Wind Turbine Rotor with Elliptic Angle Shape Variation - Antonius Hadi Sudono Putranto; Vivien Suphandani Djanali; Bambang Arip Dwiyantoro (LPPM, Institut Teknologi Sepuluh Nopember, Indonesia, 2019)
The Savonius wind turbine uses a half-cylinder blade which is often called a bucket assembled so that the cross-section forms an